Field tests and real-world exhaust gas emissions of a pure rapeseed oil-fuelled harvester in forestry: Testing a solution for combined water, soil, and climate protection. (20th January 2021) - Emberger, Peter; Hinrichs, Michael; Huber, Georg; Emberger-Klein, Agnes; Thuneke, Klaus; Pickel, Peter; Remmele, Edgar
Abstract: Using pure rapeseed oil fuel (R100) in forest machinery could be a measure that contributes to climate, water, and soil protection in forestry. However, forest machinery that is compatible with R100 is not currently available. The target of this research was to operate forest machinery with R100 in a field-test, to collect and evaluate the operational and real-world emission behaviour and to assess the environmental impact. Therefore, a modern forest harvester was modified to operate with R100 and was monitored from August 2017 until December 2018, under Bavarian working conditions. The behaviour during 2100 h of operation was mainly evaluated using information on productivity and operating fluid consumption compared to diesel fuel operation before the modifications were made. Compared to diesel fuel operation, no significant differences in the productivity of the harvester and the energy efficiency of the engine could be detected. With the fuel tempering system installed, the engine could be started at an ambient temperature as low as −20 °C. The results of the engine oil analysis and technical engine inspection after the field test indicate a failure-free operation of the engine and exhaust gas after-treatment system. Furthermore, a functional diagnosis of the harvester indicates that all of the additionally installed components were functioning and the engine, as well as the exhaust gas after-treatment system, were in an appropriate condition. The real driving emissions of nitrogen oxides, hydrocarbons, and carbon monoxide were measured at the beginning of and close to the end of the field test and compared to that of the harvester operating with diesel fuel. Statistical analysis showed no significant influence of the fuel type or the operation time with R100 on the emission behaviour. The emission results were well below the legal requirements for engine test stand measurements. Within the lifetime of the harvester it can be estimated that a turnover of 350, 000 L of diesel fuel and 700 to 1050 tonnes of greenhouse gas emissions can be avoided. For the first time, the results indicate that it is technically possible to operate a modern forest harvester with R100 (even during hard winter conditions), and this is in compliance with emission requirements and can contribute to climate, soil, and water protection. Highlights: Forest harvester was operated with pure rapeseed oil for 2100 operating hours. Productivity with pure rapeseed oil on the same level as with diesel. Real driving emissions with pure rapeseed oil comparable to diesel. 700–1050 tonnes of greenhouse gas emission can be avoided within lifetime. Turnover of 350, 000 L of diesel in forestry can be avoided within lifetime.